2001
DOI: 10.1182/blood.v97.4.1043
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of tumoral and nontumoral lymphoid cells is induced by both mdm2 and p53 antisense oligodeoxynucleotides

Abstract: Following stress signals, the p53 tumor suppressor protein plays a critical role in regulation of cell proliferation, mainly through induction of growth arrest or apoptosis. Therefore, this protein needs to be strictly regulated and numerous studies have shown that the MDM2 protein is an essential element for p53 regulation in normal cells and, most importantly, that overexpression of MDM2 is responsible for p53 inactivation in various types of tumors. A previous study showed that this is the case in some Burk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…10,12,20,28 The activation of MAPK p38 alone has been shown to induce expression of MMP-1 and -3 in an activator protein 1–independent manner by stabilizing the corresponding mRNAs in human skin fibroblasts. 29 To confirm the relative roles of JNK1 and JNK2 in the corneal epithelial stress response in vivo, we compared corneal epithelial barrier function and smoothness, as well as production of MMPs and cornified envelope precursors, following 5 days of experimental desiccation in JNK1 and JNK2 gene–deficient and wild-type C57BL/6 strains.…”
Section: Commentmentioning
confidence: 99%
“…10,12,20,28 The activation of MAPK p38 alone has been shown to induce expression of MMP-1 and -3 in an activator protein 1–independent manner by stabilizing the corresponding mRNAs in human skin fibroblasts. 29 To confirm the relative roles of JNK1 and JNK2 in the corneal epithelial stress response in vivo, we compared corneal epithelial barrier function and smoothness, as well as production of MMPs and cornified envelope precursors, following 5 days of experimental desiccation in JNK1 and JNK2 gene–deficient and wild-type C57BL/6 strains.…”
Section: Commentmentioning
confidence: 99%
“…Primary attempts were directed at antisense therapies. For example, it was observed that both antisense oligonucleotides to the mdm2 and p53 in lymphoblastoid cell line induced apoptosis in these cells only if they expressed wild-type p53 [Capoulade et al, 2001]. Cotter [1999] reviewed the potential use of antisense therapy in hematologic malignancies.…”
Section: Summary and Prospects For New Therapiesmentioning
confidence: 99%
“…Accurate transcription initiation is vital to ensure the proper expression and function of these genes (Smale and Kadonaga 2003). Mis-regulation of transcription initiation has been found to be associated with a broad range of human diseases, such as breast cancer, diabetes, kidney failure and Alzheimer's disease (Arrick et al 1991;Romeo et al 1993;Capoulade et al 2001;Sobczak and Krzyzosiak 2002;Mihailovich et al 2007). In this regard, accurate identification of TSSs and characterization of their regulated activities are essential for obtaining fundamental insights into regulatory mechanisms that determine the location and activities of transcription initiation.…”
Section: Introductionmentioning
confidence: 99%